FINANCING MANAGEMENT STRATEGY TO IMPROVE THE QUALITY OF EDUCATIONAL INSTITUTIONS IN MAN 2 BANYUWANGI - Sabar Indah Hikmawati; Suppriyadi (STAI AN-NAJAH INDONESIA MANDIRI, 2023)
Study This aim to : 1. Know understanding management strategy financing education , 2. Analyze management strategies financing For increase quality of educational institutions at MAN 2 Banyuwangi. Method used are : method qualitative with type single case study focused on management financing in education at MAN 2 Banyuwangi . Research data collected use documentation and interviews . As for analysis the data use SWOT analysis , ie analysis planning strategic use _ For monitor and evaluate environment company Good environment external and internal for something objective business certain . Result: school put forward professionalism and discipline , as well commitment task in enhancement quality school . Management strategy financing education in effort coaching participant educate done through coaching in field arts , sports , religion, scouting , language English , and personality . Management strategy financing education field facilities and infrastructure done with increase source funding , implementing improvement programs quality For support facilities and infrastructure as well as teacher welfare Conclusions and suggestions: Financing at MAN 2 Banyuwangi has been completed managed in a way professional . Based on results analysis quality education there is positive and significant relationship _ with management financing , where with management Madrasa financing is affordable plan supportive things _ enhancement quality , for example reliable financing _ will support provision infrastructure . Which supports learning , development teacher self , and achievement academic and non- academic . Keywords : Management Strategy _ Financing , Quality Improvement BIBLIOGRAPHY Augustine Sri Wahyudi. Management Strategy , Jakarta : Binarupa Aksara, 1996, p: 19 Al-Qur'an, Indonesian Translation . Ministry of Religion . 2007 Arifudin , O., Sonia, NR, Darmawan, IPA, Abbas, DS, Saputro , ANC, Poltak , H., Sundulusi , C., Darmawati , D., Harahap , E., & Sijaga , D. (2021). Management Education Financing . Bambang Supriyanto, Siti Partini Suardiman, Achadi Budi Santosa. Facilities and Infrastructure Financing Strategy to Improve Education Services in Public High Schools, 2023 . https://jim.usk.ac.id/histori/article/view/27126 Buchari Alma, Management Marketing and Services Marketing . (Bandung: Alfabeta , 2011 Burhanudin Gesi , Management and Executive , Journal Management , Vol.3 No.2, 2019., p.52 Hasbi , RPAC, & Mahmudah, FN (2020). Development Curriculum School Based Entrepreneurship at SMA Negeri 1 Temon. Nidhomul Haq: Journal Islamic Education Management , 5 (2), 180–194. Kusuma, NA (2014). Head Strategy Schools in Development Source Based Education Financing Businessman ; Case study at Nurul Hikmah Pamekasan Madura Middle School and High School. In Implementation Science . http://etheses.uinmalang . ac.id/id/ eprint /3243 , N. , Santosa, A., & Hidayati , DS Private School Financing Management Strategy in Creating Leading Schools in Muhammadiyah Vocational Schools 3 Bandung , 2023 . https://doi.org/10.31955/mea.v7i2.3389 Matin, Management Financing Education : Concept and Application , (Jakarta: PT Raja Grafindo Persada , 2014), p . 8 Megawaty , DA, Setiawansyah , S., Alita, D., & Dewi, PS (2021). Technology in management administration finance committee school For increase transparency finance . Riau Journal of Empowerment , 4 (2), 95–104. https://doi.org/10.31258/raje.4.2.95-104 Mohamed, Z.M., Abdul Majid, A.H., & Ahmad, N. (2010). Tapping new possibilities in accounting research, in qualitative research in accounting, Malaysian case. Universiti Kebangsaan Malaysia Publishers, Kuala Lumpur, Malaysia. Riinawati (2022). Strategy of Financing Management to Improve the Quality of Islamic Education Institutions . DOI: https://doi.org/10.35445/alishlah.v14i3.1519 Sri Mulyati*, Risbon Sianturi, Sarah Fauziah, Heni Widiani, Deni Ramdani , (2023). Principal's Strategy in Optimizing Financing at SDN 1 Medanglayang . Naturalistic: Journal of Research and Education and Learning Studies, 7 (2) (2023) P-ISSN: 2528-2921 E-ISSN: 2548-8589 Sudrajat , Asep Rahman. 2019.